Corrosion-resistant, wave-absorbing and resistance-reducing integrated composite material, preparation method and application of composite material in corrosion-resistant, wave-absorbing and resistance-reducing coating
By coating perfluorodecyl trimethoxysilane on carbonyl iron particles to form a composite material CIP@PDTMS, the problem of unsatisfactory wave absorption performance and poor corrosion resistance in the prior art is solved, and high efficiency is achieved The effects of wave absorption, corrosion prevention and drag reduction.
Patent Information
- Application Number
- CN202411618397.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, spherical carbonyl iron as an absorbing filler has problems such as high conductivity and poor impedance matching, which leads to poor absorption effect of electromagnetic waves and poor corrosion resistance in harsh environments.
By coating perfluorodecyl trimethoxysilane on the outer surface of carbonyl iron particles, a composite material CIP@PDTMS with a core-shell structure is formed, combining the magnetization and hysteresis loss of carbonyl iron to absorb electromagnetic waves, and utilizing the conductance and resistance of PDTMS The effect achieves wave absorption and isolates corrosive media by hydrophobicity.
It significantly improves the wave absorption and corrosion resistance of composite materials, and also has excellent drag reduction effects, solving the problems of unsatisfactory wave absorption and poor corrosion resistance in the prior art.
Smart Images

Figure CN119461496A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of functional materials, and in particular to an anti-corrosion, wave-absorbing, and drag-reducing integrated composite material, a preparation method, and its application in an anti-corrosion, wave-absorbing, and drag-reducing coating. Background Art
[0002] Organic coating refers to the coating formed by applying organic paint or plastic on the surface of parts by brushing, dipping, spraying, electrophoretic coating, electrostatic spraying, etc., and curing. It is mainly composed of fillers and adhesives. Under the premise of maintaining high protective performance, coatings are becoming more and more popular in various fields due to their economical, low cost and strong versatility.
[0003] Multifunctional coatings with anti-corrosion, wave-absorbing and drag-reducing properties are applied to the surfaces of submarines and ships to protect their metal surfaces from corrosion by seawater and attachment of marine organisms, thereby extending their service life, reducing maintenance costs, enhancing structural strength, improving navigation safety, and reducing energy consumption and environmental pollution.
[0004] Spherical carbonyl iron (CIP) is a common absorbing filler in the prior art, and has been widely studied due to its high saturation magnetization, low coercivity and moderate complex magnetic permeability. However, it has the disadvantages of high conductivity and poor impedance matching, resulting in unsatisfactory absorption of electromagnetic waves. Moreover, when CIP is used in harsh environments such as high temperature and acidity, it is easy to react with corrosive media, resulting in poor corrosion resistance of the absorbing coating and low effective bandwidth. Summary of the invention
[0005] The present application provides an anti-corrosion, wave-absorbing, and drag-reducing integrated composite material, a preparation method, and its application in an anti-corrosion, wave-absorbing, and drag-reducing coating, in order to solve the above-mentioned problems mentioned in the background technology.
[0006] On the one hand, the present application provides an integrated composite material with anti-corrosion, wave-absorbing and drag-reducing functions. The composite material is a core-shell structure, including: a carbonyl iron particle core and a perfluorodecyltrimethoxysilane shell wrapped around the outer surface of the carbonyl iron particle.
[0007] On the other hand, the present application provides a method for preparing an integrated composite material with anti-corrosion, wave-absorbing and drag-reducing functions, the method comprising the following steps:
[0008] Activation of carbonyl iron: mixing the acid with the carbonyl iron powder, and performing activation treatment on the carbonyl iron powder for 30-45 minutes to obtain activated carbonyl iron powder;
[0009] Preparation of solution A: Disperse activated carbonyl iron powder in anhydrous ethanol, add ammonia water and deionized water, stir and mix, and obtain solution A;
[0010] Preparation of solution B: dissolving perfluorodecyltrimethoxysilane in anhydrous ethanol under stirring to obtain solution B;
[0011] Preparation of composite materials: Solution A and solution B were simultaneously added dropwise to the reactor under stirring. The reaction was continued for 3 h after the addition was completed. After the reaction was completed, the solid particles were removed by magnetic separation, washed with deionized water and anhydrous ethanol for multiple times, and dried at 60-70°C for 24-30 h to obtain a core-shell composite material, namely CIP@PDTMS powder.
[0012] Optionally, in the carbonyl iron activation step, the acid concentration is 0.01 mol / L, and the acid is hydrochloric acid or nitric acid.
[0013] Optionally, in the carbonyl iron activation step, the volume weight ratio of the acid to the carbonyl iron powder is 100-130 mL: 20-25 g.
[0014] Optionally, in solution A, the weight volume ratio of activated carbonyl iron powder to anhydrous ethanol, ammonia water and deionized water is 20-25 g: 200-250 mL: 15-20 mL: 10-50 mL, and the concentration of ammonia water is 25-28 wt %.
[0015] Optionally, in solution B, the volume ratio of perfluorodecyltrimethoxysilane to anhydrous ethanol is: 25-30 mL: 120-130 mL.
[0016] Optionally, in the step of preparing the composite material, the dropping speed of solution A is 1.36-1.9 mL / min, and the dropping speed of solution B is 0.8-0.9 mL / min.
[0017] On the other hand, the present application provides an application of an integrated composite material with anti-corrosion, wave absorbing and drag reducing functions in an anti-corrosion, wave absorbing and drag reducing coating. The composite material is used to prepare the anti-corrosion, wave absorbing and drag reducing coating. The composite material is the above-mentioned composite material, or a composite material prepared using the above-mentioned preparation method.
[0018] Optionally, the anti-corrosion, wave-absorbing and drag-reducing coating includes CIP@PDTMS powder, fluorocarbon resin, dispersant, anti-settling agent, xylene, n-butanol, accelerator, curing agent and silicon dichloride.
[0019] Optionally, the weight ratio of CIP@PDTMS powder, fluorocarbon resin, dispersant, anti-settling agent, xylene, n-butanol, accelerator, curing agent and silicon dichloride is 3-4:10-12:0.2-0.32:0.2-0.25:6-8:1.7-2.0:0.3-0.33:1:3-4.
[0020] The method for preparing an integrated composite material with anti-corrosion, wave-absorbing and drag-reducing functions provided in the present application realizes the preparation of an integrated composite material with anti-corrosion, wave-absorbing and drag-reducing functions, and its application as a filler in an anti-corrosion, wave-absorbing and drag-reducing coating. Compared with the prior art, it has the following beneficial effects:
[0021] (1) The present application coats perfluorodecyltrimethoxysilane on the outer surface of carbonyl iron particles to form a composite material CIP@PDTMS with a core-shell structure. The carbonyl iron powder absorbs electromagnetic waves through magnetization and hysteresis loss, and PDTMS absorbs waves through the conductivity and resistance effects of electromagnetic waves in the material. Combining two materials with different electromagnetic wave loss types in a core-shell structure improves the shortcomings of high conductivity and poor impedance matching of carbonyl iron, and significantly enhances the wave absorption performance. At the same time, perfluorodecyltrimethoxysilane shows good hydrophobicity due to its low surface energy, which isolates the corrosive medium from direct contact with carbonyl iron and the surface of the equipment, avoids chemical and / or electrochemical corrosion on the surface of the equipment, and improves the anti-corrosion performance of the composite material CIP@PDTMS. In addition, the composite material CIP@PDTMS provided in the present application reduces the interfacial interaction between water and the coating, resulting in slippage at the solid-fluid interface, so that CIP@PDTMS has an excellent drag reduction effect. The composite material of the present application has the advantages of integrating anti-corrosion wave absorption and drag reduction functions.
[0022] (2) During the preparation of the composite material, the surface of the carbonyl iron is activated by acid, and a negatively charged hydroxyl group is obtained on the surface of the carbonyl iron. The presence of the hydroxyl group is conducive to the subsequent combination with perfluorodecyltrimethoxysilane, and then to the coating of perfluorodecyltrimethoxysilane on the surface of the carbonyl iron, thereby forming a composite material with a core-shell structure with carbonyl iron as the core and perfluorodecyltrimethoxysilane as the shell. By adding ammonia water, perfluorodecyltrimethoxysilane is hydrolyzed in the presence of ammonia water, and hydroxyl groups are further introduced on the surface of the activated carbonyl iron. The activated carbonyl iron powder is mixed and reacted under stirring to form a C=O chemical bond with the surface of the carbonyl iron, thereby forming a coating layer.
[0023] (3) By controlling the dropping speed of solution A and solution B and the stirring speed during the reaction process, the dropping speed and the stirring speed will affect the generated particle size and particle size uniformity of the composite material. Through the coordination of the two, the composite material CIP@PDTMS powder has a uniform particle size, which is beneficial to the uniformity of the coating during subsequent use, and thus helps to improve the coating's wave absorption, anti-corrosion and drag reduction properties.
[0024] (4) By using the composite material CIP@PDTMS as a filler and compounding it with other materials, a coating containing CIP@PDTMS was prepared and applied to the surface of the equipment to form a coating. The coating is a functional coating that integrates anti-corrosion, wave absorption and drag reduction functions.
[0025] (5) The present application uses low-cost carbonyl iron powder as a raw material to produce a composite material, and the operation steps are simple, which is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, a brief introduction will be given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0027] Figure 1 A synthesis mechanism diagram of CIP@PDTMS provided in one embodiment of the present application;
[0028] Figure 2 A Fourier transform infrared spectrum of CIP@PDTMS provided in one embodiment of the present application;
[0029] Figure 3 This is a SEM image of CIP@PDTMS provided in one embodiment of the present application;
[0030] Figure 4 The results of the coating anticorrosion performance provided by Example 2, Comparative Example 1 and the control group of the present application are shown in FIG. Figure 4 (a) is the electrochemical fitting equivalent circuit diagram, Figure 4 (b) is the EIS (electrochemical impedance spectroscopy) spectrum of the coating. Figure 4 (c) is the Bode diagram of the coating. Figure 4 (d) is the Bode phase angle diagram of the coating;
[0031] Figure 5 The microwave absorption performance results of the coating provided in Example 2 and Comparative Example 1 of the present application are shown in FIG. Figure 5 (a) is the 2D reflection loss contour diagram of CIP. Figure 5 (b) is the 2D reflection loss contour diagram of CIP@PDTMS.
[0032] Figure 6 The drag reduction performance results of the coating provided in Example 2 and Comparative Example 1 of the present application are shown in FIG. Figure 6 (a) is the shear stress of the three coatings at different shear rates. Figure 6 (b) shows the drag reduction effect of CIP and CIP@PDTMS coating at different shear rates. Figure 6 (c) is the viscosity of the coating surface at different shear rates;
[0033] Figure 7 The hydrophobic performance results of the coating provided in Example 2 and Comparative Example 1 of the present application are shown in FIG. Figure 7 (a) is the contact angle of water on the PVF coating, Figure 7 (b) is the contact angle of water on the CIP coating, Figure 7 (c) is the contact angle of water on CIP@PDTMS. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work also fall within the scope of protection of the present application.
[0035] On the one hand, the present application provides an integrated composite material with anti-corrosion, wave-absorbing and drag-reducing functions. The composite material is a core-shell structure, including: a carbonyl iron particle core and a perfluorodecyltrimethoxysilane shell wrapped around the outer surface of the carbonyl iron particle.
[0036] Specifically, the present application coats perfluorodecyltrimethoxysilane on the outer surface of carbonyl iron particles to form a composite material CIP@PDTMS with a core-shell structure. Carbonyl iron powder has the characteristics of low dielectric constant and high magnetic loss, and can effectively absorb electromagnetic waves through magnetization and hysteresis loss. Perfluorodecyltrimethoxysilane (PDTMS) has certain conductivity and magnetism, which enables it to achieve wave absorption through the conductivity and resistance effects of electromagnetic waves in the material, wherein the main wave absorption effect is carbonyl iron powder. The present application combines two materials of different electromagnetic wave loss types with a core-shell structure. Perfluorodecyltrimethoxysilane coating carbonyl iron can reduce the dielectric constant of carbonyl iron and increase the impedance matching degree. Compared with carbonyl iron as a wave absorbing material, the composite material has significantly enhanced wave absorbing performance.
[0037] At the same time, perfluorodecyltrimethoxysilane shows good hydrophobicity due to its low surface energy. PDTMS is coated on the surface of carbonyl iron, so that the composite material CIP@PDTMS has good hydrophobicity. When the CIP@PDTMS of the present application is coated on the surface of equipment such as submarines and ships, the hydrophobicity of CIP@PDTMS isolates water from direct contact with carbonyl iron and the surface of the equipment, and also prevents corrosive substances such as water and chloride ions in the environment from penetrating into the surface of the equipment, causing chemical and / or electrochemical corrosion with the surface of the equipment, thereby improving the anti-corrosion performance of the composite material CIP@PDTMS.
[0038] The reduction in fluid resistance of the composite material CIP@PDTMS provided in the present application is due to the low surface tension and hydrophobicity of PDTMS reducing the interfacial interaction between water and the coating, resulting in slippage at the solid-fluid interface, so that CIP@PDTMS has an excellent drag reduction effect.
[0039] The composite material CIP@PDTMS provided in the present application combines two different types of electromagnetic wave loss materials in a core-shell structure through coating treatment, thereby enhancing the wave absorption performance of the composite material. Since PDTMS is coated on the surface of carbonyl iron, the composite material CIP@PDTMS has good hydrophobicity, which improves the anti-corrosion effect of the composite material on the equipment matrix during use. At the same time, CIP@PDTMS has excellent drag reduction performance. The composite material provided in the present application is low-cost and easy to promote on a large scale.
[0040] On the other hand, the present application provides a method for preparing an integrated composite material with anti-corrosion, wave-absorbing and drag-reducing functions, the method comprising the following steps:
[0041] Activation of carbonyl iron: mixing the acid with the carbonyl iron powder, and performing activation treatment on the carbonyl iron powder for 30-45 minutes to obtain activated carbonyl iron powder;
[0042] Specifically, in the carbonyl iron activation step, impurities on the surface of the carbonyl iron, such as iron oxide and other attachments, are removed by using an acid at room temperature. At the same time, the carbonyl iron is hydrolyzed during the activation process to obtain negatively charged hydroxyl groups on the surface of the carbonyl iron. The presence of hydroxyl groups is conducive to the subsequent combination with perfluorodecyltrimethoxysilane, which is conducive to the coating of perfluorodecyltrimethoxysilane on the surface of the carbonyl iron, thereby forming a composite material with a core-shell structure with carbonyl iron as the core and perfluorodecyltrimethoxysilane as the shell.
[0043] The carbonyl iron powder is activated by acid, washed 3 times in deionized water, then washed 2-3 times in anhydrous ethanol, and dried at 70-80° C. for 12-15 hours to obtain activated carbonyl iron powder.
[0044] Preparation of solution A: Disperse activated carbonyl iron powder in anhydrous ethanol, add ammonia water and deionized water, stir and mix, and obtain solution A;
[0045] Specifically, at room temperature, ammonia water is added to the activated carbonyl iron powder to enhance the hydroxyl content and the powder is dispersed in anhydrous ethanol. Deionized water is beneficial to enhance the dispersion of hydroxyl groups. At the same time, by adding ammonia water to the activated carbonyl iron powder, hydroxyl groups are further introduced on the surface of the activated carbonyl iron, which helps the subsequent attachment of PDTMS to the surface of the carbonyl iron and is beneficial to the coating of the carbonyl iron.
[0046] Preparation of solution B: dissolving perfluorodecyltrimethoxysilane in anhydrous ethanol under stirring at room temperature to obtain solution B;
[0047] Preparation of composite materials: Solution A and solution B were simultaneously added dropwise to the reactor under stirring. The reaction was continued for 3 h after the addition was completed. After the reaction was completed, the solid particles were removed by magnetic separation, washed with deionized water and anhydrous ethanol for multiple times, and dried at 60-70°C for 24-30 h to obtain a core-shell composite material, namely CIP@PDTMS powder.
[0048] Specifically, an oil bath is heated to 43-45°C, and solution A and solution B are simultaneously added dropwise to the reactor, ethanol is used as the reaction solvent, and perfluorodecyltrimethoxysilane is hydrolyzed in the presence of ammonia water to produce hydroxyl groups, which are mixed and reacted with activated carbonyl iron powder under stirring to generate Si-O-Si, and form a C=O chemical bond with the surface of carbonyl iron to form a coating layer to obtain a reaction solution containing a composite material. Since the composite material has magnetic properties, the composite material solid particles are taken out by magnetic separation, washed with deionized water and anhydrous ethanol for multiple times, unreacted raw materials are removed, and dried to obtain CIP@PDTMS powder.
[0049] Among them, magnetic separation refers to the response of the substance to the magnetic field, that is, different substances have different magnetization degrees to the magnetic field. According to the magnetic difference of the substance, the target substance is selectively adsorbed by the magnetic material to achieve the purpose of separation. A magnet is used to adsorb the prepared CIP@PDTMS powder through the different responses of carbonyl iron and other substances to the magnet, so as to achieve the separation of CIP@PDTMS powder. Magnetic separation is a process well known and routinely operated by those skilled in the art, and will not be described in detail in this application. Among them, the particle size of the carbonyl iron particles is 0.5-20μm, and the particle size of the CIP@PDTMS provided in this application is 0.5-20μm. The above-mentioned normal temperature refers to a temperature of 18-30°C.
[0050] The present application realizes the preparation of a core-shell composite material of carbonyl iron coated with perfluorodecyltrimethoxysilane through the above scheme. Impurities on the surface of carbonyl iron are removed by using acid, and negatively charged hydroxyl groups are obtained on the surface of carbonyl iron. The presence of hydroxyl groups is conducive to the subsequent combination with perfluorodecyltrimethoxysilane, which is conducive to the coating of perfluorodecyltrimethoxysilane on the surface of carbonyl iron, thereby forming a composite material with a core-shell structure with carbonyl iron as the core and perfluorodecyltrimethoxysilane as the shell. By adding ammonia water, perfluorodecyltrimethoxysilane is hydrolyzed, and hydroxyl groups are further introduced, which promotes perfluorodecyltrimethoxysilane to adhere to the surface of carbonyl iron, form C=O chemical bonds with the surface of carbonyl iron, and form a coating layer. Starting from the two aspects of composition and structure, the present application combines two different types of electromagnetic wave loss materials in a core-shell structure to prepare a composite material CIP@PDTMS that integrates anti-corrosion wave absorption and drag reduction functions.
[0051] Optionally, in the carbonyl iron activation step, the acid concentration is 0.01 mol / L, and the acid is hydrochloric acid or nitric acid.
[0052] Specifically, acid is used to remove impurities and iron oxide on the surface of carbonyl iron, so that the surface of carbonyl iron is activated to obtain more hydroxyl groups, thereby increasing the number of active sites on the surface of carbonyl iron for reacting with perfluorodecyltrimethoxysilane, thereby facilitating the coating of carbonyl iron with perfluorodecyltrimethoxysilane.
[0053] Optionally, in the carbonyl iron activation step, the volume weight ratio of the acid to the carbonyl iron powder is 100-130 mL: 20-25 g.
[0054] Specifically, by controlling the volume weight ratio of the acid to the carbonyl iron powder, not only the purpose of activating the surface of the carbonyl iron is achieved, but also the waste of raw materials is avoided.
[0055] Optionally, in solution A, the weight volume ratio of activated carbonyl iron powder to anhydrous ethanol, ammonia water and deionized water is 20-25 g: 200-250 mL: 15-20 mL: 10-50 mL, and the concentration of ammonia water is 25-28 wt %.
[0056] Specifically, anhydrous ethanol is used as a dispersion reaction solvent, and ammonia water is added to solution A. Ammonia water molecules contain lone pairs of electrons, which can produce a slight coordination effect with silanols, thereby promoting the hydrolysis reaction, so that perfluorodecyltrimethoxysilane is hydrolyzed to further introduce hydroxyl groups and disperse them in anhydrous ethanol. Deionized water is beneficial to enhance the dispersion of hydroxyl groups. Controlling the weight-to-volume ratio of activated carbonyl iron powder to anhydrous ethanol, ammonia water, and deionized water not only helps the subsequent attachment of PDTMS to the surface of carbonyl iron, but also facilitates the coating of carbonyl iron and avoids waste of raw materials.
[0057] Optionally, in solution B, the volume ratio of perfluorodecyltrimethoxysilane to anhydrous ethanol is: 25-30 mL: 120-130 mL.
[0058] Specifically, controlling the volume ratio of perfluorodecyltrimethoxysilane to anhydrous ethanol is not only beneficial to the dispersion of perfluorodecyltrimethoxysilane, but also beneficial to the hydrolysis of perfluorodecyltrimethoxysilane, thereby promoting the coating of carbonyl iron by PDTMS.
[0059] In the preparation step of the composite material, the dripping speed of solution A is controlled to be 1.36-1.9 mL / min, and the dripping speed of solution B is controlled to be 0.8-0.9 mL / min. The stirring speed is controlled to be 450-460 r / min. The dripping speed and stirring speed will affect the generated particle size and particle size uniformity of the composite material. Through the combination of the two, the composite material CIP@PDTMS powder has a uniform particle size, which is beneficial to the uniformity of the coating during subsequent use, thereby helping to improve the coating's wave absorption, anti-corrosion and drag reduction properties.
[0060] On the other hand, the present application provides an application of an integrated composite material with anti-corrosion, wave absorbing and drag reducing functions in an anti-corrosion, wave absorbing and drag reducing coating. The composite material is used to prepare the anti-corrosion, wave absorbing and drag reducing coating. The composite material is the above-mentioned composite material, or a composite material prepared using the above-mentioned preparation method.
[0061] Specifically, the composite material CIP@PDTMS provided in the present application is used as a filler and compounded with other materials to prepare a coating containing CIP@PDTMS, which is applied to the surface of the equipment to form a coating, which is a functional coating integrating anti-corrosion, wave absorption and drag reduction functions.
[0062] Optionally, the anti-corrosion, wave-absorbing and drag-reducing coating includes CIP@PDTMS powder, fluorocarbon resin, dispersant, anti-settling agent, xylene, n-butanol, accelerator, curing agent and silicon dichloride.
[0063] Specifically, CIP@PDTMS powder is used as a filler to improve the anti-corrosion, wave absorption and drag reduction properties of the coating. Fluorocarbon resin (PVF) is the base material of the coating and is also the film-forming material of the coating. It forms a protective film on the surface of the substrate to isolate the substrate surface from the external environment, and has good chemical resistance, weather resistance, flexibility and gloss. Dispersants are conducive to the uniform dispersion of the various components in the coating in the base material fluorocarbon resin, which is conducive to the uniformity of the coating and ensures the stability of the functions of each position of the coating. Anti-settling agents help solid materials remain suspended in the coating, thereby improving the coating effect during the coating process.
[0064] Xylene is mainly used as a solvent and diluent in paint. It can increase the fluidity of the paint, help the paint adhere better to the surface of the object, and improve the drying speed and glossiness of the paint. It can also adjust the volatilization rate of the paint, affect the surface tension and adhesion of the paint, thereby improving the process performance of the paint and reducing surface defects of the coating. Butanol makes the paint smoother and easier to apply, and can also promote the drying of the paint, making the paint quality more stable.
[0065] Accelerators can reduce the surface tension and viscosity of the coating, making it easier to apply the coating to the substrate surface, while also improving the durability and adhesion of the coating. Curing agents can significantly accelerate the drying and curing process of the coating. Silica can significantly improve the physical properties of the coating, such as improving the adhesion, toughness, elasticity, aging resistance, and UV resistance of the coating, while also acting as a skeleton and filler, reducing the amount of fluorocarbon resin used and reducing production costs.
[0066] Among them, the dispersant was purchased from BYK-190 of BYK Chemical Co., Ltd. of Germany, the anti-settling agent was purchased from BYK-410 of BYK Chemical Co., Ltd. of Germany, and the accelerator was BYK-4511. The curing agent used was isocyanate curing agent HT-100.
[0067] Optionally, the weight ratio of CIP@PDTMS powder, fluorocarbon resin, dispersant, anti-settling agent, xylene, n-butanol, accelerator, curing agent and silicon dichloride is 3-4:10-12:0.2-0.32:0.2-0.25:6-8:1.7-2.0:0.3-0.33:1:3-4.
[0068] Specifically, CIP@PDTMS powder, fluorocarbon resin, dispersant, anti-settling agent, xylene, n-butanol, accelerator, curing agent and silicon dichloride are stirred and mixed according to a weight ratio to obtain a coating, and then the coating is applied to the surface of the substrate by spraying, brushing, scraping, spin coating, etc. to obtain an anti-corrosion, wave-absorbing and drag-reducing coating. The thickness of the anti-corrosion, wave-absorbing and drag-reducing coating is determined according to actual working conditions, and this application does not limit the coating thickness.
[0069] The technical solution of the present application is described in detail below with reference to specific embodiments.
[0070] Example 1
[0071] A method for preparing a composite material with integrated anti-corrosion, wave-absorbing and drag-reducing functions and its application in an anti-corrosion, wave-absorbing and drag-reducing coating comprises the following steps:
[0072] (1) Activation of carbonyl iron: At room temperature, 0.01 mol / L nitric acid was mixed with carbonyl iron powder, and the carbonyl iron powder was activated for 30 min. The powder was then washed three times in deionized water, then washed twice in anhydrous ethanol, and dried at 70° C. for 12 hours to obtain activated carbonyl iron powder.
[0073] The volume weight ratio of nitric acid to carbonyl iron powder is 100:20g. The carbonyl iron uses pentacarbonyl iron, and the particle size of carbonyl iron particles is 0.5-20μm.
[0074] (2) Preparation of Solution A: At room temperature, activated carbonyl iron powder is dispersed in anhydrous ethanol, and ammonia water and deionized water are added, and stirred to obtain Solution A.
[0075] The weight volume ratio of activated carbonyl iron powder to anhydrous ethanol, ammonia water and deionized water is 20 g: 200 mL: 15 mL: 10 mL, and the concentration of ammonia water is 25-28 wt %.
[0076] (3) Preparation of Solution B: Perfluorodecyltrimethoxysilane was dissolved in anhydrous ethanol under stirring at room temperature to obtain Solution B. The volume ratio of perfluorodecyltrimethoxysilane to anhydrous ethanol was 25 mL:120 mL.
[0077] (4) Preparation of composite materials: Heat the oil bath to 43°C, and add solution A and solution B to the reactor at the same time under stirring. The drop rate of solution A is 1.36 mL / min, and the drop rate of solution B is 0.8 mL / min. The stirring speed is controlled at 450 r / min. After the drop addition is completed, the reaction is continued for 3 hours. After the reaction is completed, the solid particles are removed by magnetic separation, washed with deionized water and anhydrous ethanol for multiple times, and dried at 60°C for 24 hours to obtain a core-shell composite material, namely CIP@PDTMS powder.
[0078] (5) CIP@PDTMS powder, fluorocarbon resin, xylene, n-butanol, dispersant, anti-settling agent, and accelerator were stirred at a speed of 2000 r / min for 10 min, and then a curing agent and silicon dichloride were added, and stirred at a speed of 2000 r / min for 10 min to obtain a coating. The coating was evenly sprayed onto the tinplate using a spray gun to obtain an anti-corrosion, wave-absorbing, and drag-reducing coating.
[0079] The weight ratio of CIP@PDTMS powder, fluorocarbon resin, dispersant, anti-settling agent, xylene, n-butanol, accelerator, curing agent and silicon dichloride is 3:10:0.2:0.2:6:1.7:0.3:1:3.
[0080] Example 2
[0081] A method for preparing a composite material with integrated anti-corrosion, wave-absorbing and drag-reducing functions and its application in an anti-corrosion, wave-absorbing and drag-reducing coating comprises the following steps:
[0082] The difference from Example 1 is that:
[0083] (1) Activation of carbonyl iron: At room temperature, 0.01 mol / L nitric acid was mixed with carbonyl iron powder, and the carbonyl iron powder was activated for 40 min. The powder was then washed three times in deionized water, then washed three times in anhydrous ethanol, and dried at 75° C. for 13 hours to obtain activated carbonyl iron powder.
[0084] The volume weight ratio of nitric acid to carbonyl iron powder is 120 mL:20 g.
[0085] (2) Preparation of solution A: The weight volume ratio of activated carbonyl iron powder to anhydrous ethanol, ammonia water, and deionized water is 22 g: 230 mL: 15 mL: 10 mL, and the concentration of ammonia water is 25-28 wt %.
[0086] (3) Preparation of solution B: The volume ratio of perfluorodecyltrimethoxysilane to anhydrous ethanol is 30 mL:125 mL.
[0087] (4) Preparation of composite materials: Heat the oil bath to 44°C, and add solution A and solution B to the reactor at the same time under stirring. The drop rate of solution A is 1.6 mL / min, and the drop rate of solution B is 0.85 mL / min. The stirring speed is controlled at 450 r / min. After the drop addition is completed, the reaction is continued for 3 hours. After the reaction is completed, the solid particles are removed by magnetic separation, washed with deionized water and anhydrous ethanol for multiple times, and dried at 70°C for 24 hours to obtain a core-shell composite material, namely CIP@PDTMS powder.
[0088] (5) CIP@PDTMS powder, fluorocarbon resin, xylene, n-butanol, dispersant, anti-settling agent, and accelerator were stirred at a speed of 2000 r / min for 10 min, and then a curing agent and silicon dichloride were added, and stirred at a speed of 2000 r / min for 10 min to obtain a coating. The coating was evenly sprayed onto the tinplate using a spray gun to obtain an anti-corrosion, wave-absorbing, and drag-reducing coating.
[0089] The weight ratio of CIP@PDTMS powder, fluorocarbon resin, dispersant, anti-settling agent, xylene, n-butanol, accelerator, curing agent and silicon dichloride is 3.5:11:0.25:0.23:7:1.8:0.32:1:3.5.
[0090] Example 3
[0091] A method for preparing a composite material with integrated anti-corrosion, wave-absorbing and drag-reducing functions and its application in an anti-corrosion, wave-absorbing and drag-reducing coating comprises the following steps:
[0092] The difference from Example 1 is that:
[0093] (1) Activation of carbonyl iron: At room temperature, 0.01 mol / L nitric acid was mixed with carbonyl iron powder, and the carbonyl iron powder was activated for 45 min. The powder was then washed three times in deionized water, then washed three times in anhydrous ethanol, and dried at 80° C. for 15 hours to obtain activated carbonyl iron powder.
[0094] The volume weight ratio of nitric acid to carbonyl iron powder is 130 mL:25 g.
[0095] (2) Preparation of solution A: The weight volume ratio of activated carbonyl iron powder to anhydrous ethanol, ammonia water, and deionized water is 25 g: 250 mL: 20 mL: 50 mL, and the concentration of ammonia water is 25-28 wt %.
[0096] (3) Preparation of Solution B: Perfluorodecyltrimethoxysilane was dissolved in anhydrous ethanol under stirring at room temperature to obtain Solution B. The volume ratio of perfluorodecyltrimethoxysilane to anhydrous ethanol was 30 mL:130 mL.
[0097] (4) Preparation of composite materials: Heat the oil bath to 45°C, and add solution A and solution B to the reactor at the same time under stirring. The drop rate of solution A is 1.9 mL / min, and the drop rate of solution B is 0.9 mL / min. The stirring speed is controlled at 460 r / min. After the drop addition is completed, the reaction is continued for 3 hours. After the reaction is completed, the solid particles are removed by magnetic separation, washed with deionized water and anhydrous ethanol for multiple times, and dried at 70°C for 30 hours to obtain a core-shell composite material, namely CIP@PDTMS powder.
[0098] (5) CIP@PDTMS powder, fluorocarbon resin, xylene, n-butanol, dispersant, anti-settling agent, and accelerator were stirred at a speed of 2000 r / min for 10 min, and then a curing agent and silicon dichloride were added, and stirred at a speed of 2000 r / min for 10 min to obtain a coating. The coating was evenly sprayed onto the tinplate using a spray gun to obtain an anti-corrosion, wave-absorbing, and drag-reducing coating.
[0099] The weight ratio of CIP@PDTMS powder, fluorocarbon resin, dispersant, anti-settling agent, xylene, n-butanol, accelerator, curing agent and silicon dichloride is 4:12:0.32:0.25:8:2.0:0.33:1:4.
[0100] Comparative Example 1
[0101] The difference from Example 2 is that:
[0102] The carbonyl iron powder is not subjected to coating treatment and is directly used as filler to prepare the coating.
[0103] (5) According to weight, carbonyl iron (CIP) powder, fluorocarbon resin, xylene, n-butanol, dispersant, anti-settling agent, and accelerator are stirred at a speed of 2000 r / min for 10 minutes, and then a curing agent and silicon dichloride are added, and stirred at a speed of 2000 r / min for 10 minutes to obtain a coating. The coating is evenly sprayed onto the tinplate using a spray gun to obtain a CIP coating.
[0104] Control group
[0105] The difference from Example 2 is that:
[0106] No filler was added to the paint in this control group.
[0107] Fluorocarbon resin 41215, xylene, n-butanol, dispersant, anti-settling agent and accelerator were mixed and stirred at a speed of 2000 r / min for 10 minutes. Then, curing agent and silicon dichloride were added and stirred at a speed of 2000 r / min for 10 minutes to obtain the coating. The coating was evenly sprayed onto the tinplate using a spray gun to obtain a control group coating (PVF coating).
[0108] Experimental Example 1
[0109] The composite material CIP@PDTMS powder can be prepared through the schemes provided in Examples 1 to 3. Taking the CIP@PDTMS obtained in Example 2 as an example, CIP@PDTMS is characterized.
[0110] Structural analysis of CIP@PDTMS
[0111] The structure of CIP@PDTMS obtained in Example 2 was detected by Fourier transform infrared spectroscopy (FTIR) and compared with carbonyl iron CIP. Figure 2 Results shown.
[0112] Depend on Figure 2 It can be seen that at 1284cm -1 C=O stretching vibration appears at 1046cm -1 、876cm -1 is Si-O-Si, at 950cm -1 ,1210 -1 The characteristic peak of Si-C appears at , indicating the preparation of CIP@PDTMS.
[0113] Experimental Example 2
[0114] CIP@PDTMS morphology analysis
[0115] The morphology of CIP@PDTMS obtained in Example 2 was examined by scanning electron microscopy (SEM), and the following was obtained: Figure 3 Results shown.
[0116] observe Figure 3 It can be seen that CIP@PDTMS is in spherical particles. At the same time, from the EDS element distribution, perfluorodecyltrimethoxysilane is coated on the surface of carbonyl iron, realizing the preparation of CIP@PDTMS.
[0117] Experimental Example 3
[0118] CIP@PDTMS coating anticorrosion performance test
[0119] The coatings provided in Example 2, Comparative Example 1 and the control group were sprayed uniformly onto the tinplate using a spray gun to prepare a coating with a thickness of 50 μm. The coatings in Example 2, Comparative Example 1 and the control group were recorded as CIP@PDTMS, CIP and PVF, respectively.
[0120] The corrosion resistance was measured using a CHI660E electrochemical workstation. A three-electrode detection system was used, with a saturated KCl electrode as the reference electrode and a platinum sheet as the counter electrode. The effective surface area of the sample was 1 cm 2 To achieve electrochemical stability, the three groups of coatings were immersed in 3.5wt.% NaCl solution for 24 h and then subjected to open circuit potential (OCP) test for 1 h. -2 –10 5 Electrochemical impedance spectroscopy was obtained in the Hz frequency range. The polarization curve was measured in the voltage range of -0.2 to 0.2 V (relative to OCP) at a scan rate of 1 mV / s. Then, an equivalent circuit diagram was established, and the data was fitted using ZView software to analyze the corrosion process and compare the fitting parameters, further quantifying the anti-corrosion performance of the coating. The results are as follows Figure 4 As shown, Figure 4 (a) is the electrochemical fitting equivalent circuit diagram of the coating. Figure 4 (b) is the EIS (electrochemical impedance spectroscopy) spectrum of the coating. Figure 4 (c) is the Bode diagram of the coating. Figure 4 (d) is the Bode phase angle diagram of the coating.
[0121] like Figure 4 As shown in (b), the dotted line and solid line represent the measured data and the fitted data respectively. Figure 4In (b), the larger the capacitance arc radius, the better the corrosion resistance of the coating. It can be observed that after immersion for 24 hours, the EIS graphs of the three groups of coatings all showed a single capacitance arc, indicating the existence of a single time constant and indicating that the coating prevented direct contact between the corrosive medium and the metal substrate. Comparing the three curves, it can be seen that the capacitance arc diameters of the three groups of coatings follow the rule of increasing in sequence for CIP, PVF and CIP@PDTMS, indicating that the CIP@PDTMS coating has the best corrosion resistance and the CIP coating has the worst corrosion resistance.
[0122] Corrosion reactions generally occur in the low-frequency region, and the impedance modulus at low frequency (Zf = 0.01 Hz) is an important indicator for evaluating the corrosion resistance of samples. Figure 4 In (c), the impedance moduli of CIP@PDTMS, PVF and CIP coatings in the low frequency region (Zf = 0.01 Hz) decrease in turn, which are 2.1×10 8 Ω·cm 2 , 7.1×10 7 Ω·cm 2 and 7.4×10 6 Ω·cm 2 From the phase angle diagram ( Figure 4 Similar results were also observed in (d). A phase angle close to 90° in a wide frequency range indicates excellent barrier properties against corrosive media. CIP@PDTMS and PVF coatings exhibited higher phase angles of 74° and 70°, respectively, while the phase angle of the CIP coating was only 59°. The above results all indicate that the CIP@PDTMS coating prepared in this application has the best anti-corrosion performance.
[0123] Experimental Example 4
[0124] CIP@PDTMS coating microwave absorption performance test
[0125] Since pure PVF coating has no wave absorption performance, the wave absorption performance test was not performed. The coatings prepared in Example 2 and Comparative Example 1 were sprayed onto the surface of a polytetrafluoroethylene (PTFE) substrate to prepare a coating with a thickness of about 1.5 mm for testing the wave absorption performance.
[0126] The coating with a thickness of about 1.5 mm was separated from the PTFE substrate and rolled into a coaxial ring with an inner diameter of 3 mm, an outer diameter of 7 mm and a height of about 1.5 mm using a mold. The wave absorption performance was tested using a vector network analyzer (model E5063A). The results are as follows: Figure 5 Two-dimensional reflection loss (RL) plots of CIP and CIP@PDTMS coatings (thickness ranges from 0.1 to 5.0 mm) in the frequency range of 2–18 GHz are shown. Figure 5 (a) is the 2D reflection loss contour diagram of CIP. Figure 5 (b) is the 2D reflection loss contour diagram of CIP@PDTMS.
[0127] Figure 5 As can be seen from (a), the effective absorption bandwidth (EAB) of the CIP coating is narrow at a thickness of 1.1 mm, only 6 GHz. The minimum RL at a thickness of 3.1 mm is -50.6 dB. Figure 5 (b) shows that after the CIP is coated with organic fluoride, the wave absorption performance is significantly enhanced. At a thickness of 1.2 mm, EAB reaches 8.9 GHz (9.1-18 GHz), covering the entire Ku band, showing very excellent wave absorption performance. It can be inferred that compared with PVF and CIP coatings, the corrosion resistance and wave absorption performance of CIP@PDTMS coating are significantly improved.
[0128] Experimental Example 5
[0129] Drag reduction performance test of CIP@PDTMS coating
[0130] The coatings provided in Example 2, Comparative Example 1 and the control group were sprayed uniformly onto tinplate using a spray gun to prepare a coating with a thickness of 50 μm. The coatings in Example 2, Comparative Example 1 and the control group were recorded as CIP@PDTMS, CIP and PVF, respectively. The Couette flow field constructed by the plate-plate mode of the rotational rheometer was used to measure the drag reduction performance of the coating at different shear rates. The shear rate of the upper plate was 15 s -1 The interval is stepped from 0s -1 Increase to 140s -1 The test process is as follows: a stainless steel rotor with a diameter of 25 mm is connected to the rotating shaft, the coating is fixed on the bottom plate, the gap between the rotor and the coating is adjusted to 1 mm, and deionized water is injected into the gap as the working fluid medium using a syringe. Each sample is measured 3 times and the standard deviation is calculated. The results are as follows Figure 6 shown.
[0131] Figure 6 (a) is the shear stress of the three coatings at different shear rates. Figure 6 (b) shows the drag reduction effect of CIP and CIP@PDTMS coating at different shear rates. Figure 6 (c) is the viscosity of the coating surface at different shear rates.
[0132] The designed coating can achieve drag reduction at the solid-liquid interface. The drag reduction effect of the coating on distilled water at various shear rates was measured using Couette flow established by the plate-plate mode of a rotational rheometer. Figure 6In (a), at a given constant energy, the shear stress of CIP and CIP@PDTMS coatings is shown to be lower than that of pure PVF. This indicates that the momentum transfer at the solid-liquid interface is reduced in CIP and CIP@PDTMS coatings.
[0133] The drag reduction efficiency (DR) is determined by the shear stress. The calculation formula is as follows: where τc and τs are the shear stresses obtained when the fluid medium flows through the blank coating and the composite coating surface respectively:
[0134]
[0135] like Figure 6 From (b), we can see that the drag reduction efficiency of CIP@PDTMS coating is about 38%-59%, while that of CIP coating is about 8-22%. Obviously, the drag reduction effect of CIP@PDTMS coating is much greater than that of CIP coating.
[0136] To further understand the occurrence of fluid drag reduction, the change in dynamic viscosity was studied. The dynamic viscosity of the working fluid flowing over the coating surface is shown in Figure 6 (c). The shear-thinning property causes its viscosity to fluctuate with increasing shear rate. In addition, compared with PVF, CIP and CIP@PDTMS coatings have lower average dynamic viscosity, which means that less energy needs to be provided for momentum transfer between adjacent fluid layers, thereby reducing the kinetic resistance of flow between fluids. In the CIP@PDTMS coating, the reduction in fluid resistance is due to the fact that the low surface tension and hydrophobicity of PDTMS reduce the interfacial interaction between distilled water and the coating, resulting in slip at the solid-fluid interface. In summary, the CIP@PDTMS coating has an excellent drag reduction effect.
[0137] Experimental Example 6
[0138] CIP@PDTMS coating hydrophobicity test
[0139] The hydrophobicity of the three groups of coatings was evaluated by measuring the contact angle (CA) of a water drop on the coating using a contact angle tester. Figure 7 shown. Figure 7 (a) is the contact angle of water on PVF, Figure 7 (b) is the contact angle of water on CIP, Figure 7 (c) is the contact angle of water on CIP@PDTMS.
[0140] observe Figure 7 It was found that pure PVF coating ( Figure 7 (a)) and CIP coating ( Figure 7The hydrophobic angles of (b)) are 75.06° and 89.66° respectively, while the contact angle of CIP@PDTMS coating is 109.64°, which further illustrates that after CIP is wrapped with PFOTES, the perfluorodecyl chain in PFOTES makes CIP@PDTMS coating have excellent hydrophobicity. At the same time, the higher hydrophobicity helps to isolate water from direct contact with carbonyl iron and equipment surface, and also prevents corrosive substances such as water and chloride ions in the environment from penetrating into the equipment surface and chemically and / or electrochemically corroding the equipment surface, which promotes the corrosion resistance and drag reduction of CIP@PDTMS coating.
[0141] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, ordinary technicians in the field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. An integrated composite material with anti-corrosion, wave-absorbing and drag-reducing functions, characterized in that: The composite material is a core-shell structure, comprising: a carbonyl iron particle core and a perfluorodecyltrimethoxysilane shell wrapped on the outer surface of the carbonyl iron particle.
2. A method for preparing an integrated composite material with anti-corrosion, wave-absorbing and drag-reducing functions, characterized in that: The preparation method comprises the following steps: Activation of carbonyl iron: mixing an acid with carbonyl iron powder, and subjecting the carbonyl iron powder to an activation treatment for 30-45 minutes to obtain activated carbonyl iron powder; Preparation of solution A: dispersing the activated carbonyl iron powder into anhydrous ethanol, adding ammonia water and deionized water, stirring and mixing, to obtain the solution A; Preparation of solution B: dissolving perfluorodecyltrimethoxysilane in anhydrous ethanol under stirring to obtain the solution B; Preparation of composite materials: Under stirring, the solution A and the solution B are simultaneously added dropwise to the reactor. After the addition is completed, the reaction is continued for 3 hours. After the reaction is completed, the solid particles are removed by magnetic separation, washed with deionized water and anhydrous ethanol for multiple times, and dried at 60-70°C for 24-30 hours to obtain the core-shell composite material, i.e., CIP@PDTMS powder.
3. The method for preparing the integrated composite material with anti-corrosion, wave-absorbing and drag-reducing functions according to claim 2, characterized in that: In the carbonyl iron activation step, the concentration of the acid is 0.01 mol / L, and the acid is hydrochloric acid or nitric acid.
4. The method for preparing the integrated composite material with anti-corrosion, wave-absorbing and drag-reducing functions according to claim 2, characterized in that: In the carbonyl iron activation step, the volume weight ratio of the acid to the carbonyl iron powder is 100-130 mL: 20-25 g.
5. The method for preparing the integrated composite material with anti-corrosion, wave-absorbing and drag-reducing functions according to claim 2, characterized in that: In the solution A, the weight volume ratio of the activated carbonyl iron powder to the anhydrous ethanol, the ammonia water, and the deionized water is 20-25 g: 200-250 mL: 15-20 mL: 10-50 mL, and the concentration of the ammonia water is 25-28 wt %.
6. The method for preparing the integrated composite material with anti-corrosion, wave-absorbing and drag-reducing functions according to claim 2, characterized in that: In the solution B, the volume ratio of the perfluorodecyltrimethoxysilane to the anhydrous ethanol is 25-30 mL:120-130 mL.
7. The method for preparing the integrated composite material with anti-corrosion, wave-absorbing and drag-reducing functions according to claim 2, characterized in that: In the step of preparing the composite material, the droplet speed of the solution A is 1.36-1.9 mL / min, and the droplet speed of the solution B is 0.8-0.9 mL / min.
8. Application of an anti-corrosion, wave-absorbing and drag-reducing integrated composite material in an anti-corrosion, wave-absorbing and drag-reducing coating, characterized in that: The composite material is used for preparing an anti-corrosion, wave-absorbing and drag-reducing coating. The composite material is the composite material described in claim 1 above, or a composite material prepared by the preparation method described in any one of claims 2 to 7 above.
9. The use of the anti-corrosion, wave-absorbing and drag-reducing integrated composite material according to claim 8 in an anti-corrosion, wave-absorbing and drag-reducing coating, characterized in that: The anti-corrosion, wave-absorbing and drag-reducing coating comprises the CIP@PDTMS powder, fluorocarbon resin, a dispersant, an anti-settling agent, xylene, n-butanol, an accelerator, a curing agent and silicon dichloride.
10. The use of the anti-corrosion, wave-absorbing and drag-reducing integrated composite material according to claim 9 in an anti-corrosion, wave-absorbing and drag-reducing coating, characterized in that: The weight ratio of the CIP@PDTMS powder, the fluorocarbon resin, the dispersant, the anti-settling agent, the xylene, the n-butanol, the accelerator, the curing agent and the silicon dichloride is 3-4:10-12:0.2-0.32:0.2-0.25:6-8:1.7-2.0:0.3-0.33:1:3-4.